Emotional intelligence as a protective factor against depression, anxiety, stress and burnout in university students - Aguilar-Priego, Lizbeth (2023)
University students face several challenges, which is why interest in the study of mental health has been increasing. Thus, the objective of this research was to identify the prevalence of depression, anxiety, stress and burnout in university students at a Mexican public university, as well as to determine their relationship with emotional intelligence as a possible protective factor. From a quantitative, non-experimental, cross-sectional design approach, 573 students participated, 421 women (73.5%) and 152 men (26.5%) with an average age of 21 years. A low prevalence of depression, anxiety and stress was found. Regarding sex differences, in the male subsample there were higher scores in knowledge of their own emotions (U=25948.0, Z=-3.46, p=.00),use of emotions (U=28648.0, Z=-1.91, p=. 05) and emotional regulation (U=23753.0, Z=-4.72, p=.00), while women reported higher rates of depression (U=26502.0, Z=-3.14, p=.02), anxiety (U=22767.0, Z=-5.28, p=.00) and stress (U=23379.0, Z=-4.93, p=.00). Regarding the correlations, in women the association of anxiety with depression (rho=.698**, p<.01) and stress with depression (rho=.746**, p<.01) stands out, while in men depression was associated with anxiety (rho=.614**, p<.01) and with stress (rho=.627**, p<.01) and anxiety with stress (rho=.785**, p<.01). It is concluded that emotional intelligencecould act as a protective factor, since the population with emotional intelligence is more likely to have a high level of anxietyand anxiety with stress (rho=.785**, p<.01). It is concluded that emotional intelligence could act as a protective factor, since the population that shows a higher emotional intelligence shows less symptoms of depression, anxiety, stress and/or burnout, which is very important because when they are related to each other, they derive in an undesirable risk in university students.